THE ROLE OF BLACK TEA AND PINEAPPLE JUICE AS NEGATIVE ORAL CONTRASTS ON MAGNETIC RESONANCE CHOLANGIOPANCREATOGRAPHY (MRCP) EXAMINATION - Hapsari, Shinta J.; Latifah, Risalatul; Muhaimin, Muhaimin (Journal of Vocational Health Studies, 2019)
Background: Magnetic resonance cholangiopancreatography examination is a superior examination in the detection of anatomic structures or pathological abnormalities in the human pancreatobiliary system. This examination is recommended to use negative oral contrast which aims to eliminate gastrointestinal signals that are around the pancreatobiliary system which can be a barrier to the visualization of the pancreatobiliary tract. Materials that can be used as oral contrast contrast must be able to survive for a long time in the gastrointestinal tract and contain elements of iron (Fe) and Manganese (Mn). The high Mn content of black and pineapple juice and its abundance need to be explored as contrast oral negative. Purpose: To prove the role of pineapple juice and black tea which are natural ingredients of negative oral contrast in the visualization of the pancreatobiliary system on MRCP examination. Method: Experimental quasy studies have been carried out on 9 samples prospectively. Each sample underwent MRCP examination with three treatments, namely given black tea, pineapple juice and plain water. The image results from the three treatments were assessed by Radiology Doctors to assess the quality of their image. Result: The results showed that black tea was more effective in providing optimal image results on MRCP examination than pineapple juice and without using oral contrast contrast. The metal content of negative oral contrast can cause magnetic susceptibility which is characterized by the presence of shortening at the time of T2 relaxation. Negative contrast agents affect signal intensity usually by shortening T2 or T2 *, as an effect, areas of concern, especially areas with negative contrast agents will experience darkening. Conclusion: Black tea is effectively used as a negative oral contrat on MRCP examination.